Dynamic Profile of CD4+ T-Cell-Associated Cytokines/Chemokines following Murine Myocardial Infarction/Reperfusion - Dongsheng Yuan; Jinjun Tie; Zhican Xu; Guanya Liu; Xinyu Ge; Zhulin Wang; Xumin Zhang; Shiyu Gong; Gang Liu; Qingshu Meng; Fang Lin; Zhongmin Liu; et al. (Mediators of Inflammation)
CD4+ T-cells play crucial roles in the injured heart. However, the way in which different CD4+ T subtypes function in the myocardial infarction/reperfusion (MI/R) heart is still poorly understood. We aimed to detect the dynamic profile of distinct CD4+ subpopulation-associated cytokines/chemokines by relying on a closed-chest acute murine MI/R model. The protein levels of 26 CD4+ T-cell-associated cytokines/chemokines were detected in the heart tissues and serum of mice at day 7 and day 14 post-MI/R or sham surgery. The mRNA levels of IL-4, IL-6, IL-13, IL-27, MIP-1β, MCP-3, and GRO-α were measured in blood mononuclear cells. The protein levels of IL-4, IL-6, IL-13, IL-27, MIP-1β, MCP-3, and GRO-α increased in both injured heart tissues and serum, while IFN-γ, IL-12P70, IL-2, IL-1β, IL-18, TNF-α, IL-5, IL-9, IL-17A, IL-23, IL-10, eotaxin, MIP-1α, RANTES, MCP-1, and MIP-2 increased only in MI/R heart tissues in the day 7 and day 14 groups compared to the sham group. In serum, the IFN-γ, IL-23, and IL-10 levels were downregulated in the MI/R model at both day 7 and day 14 compared to the sham. Compared with the protein expressions in injured heart tissues at day 7, IFN-γ, IL-12P70, IL-2, IL-18, TNF-α, IL-6, IL-4, IL-5, IL-9, IL-17A, IL-23, IL-27, IL-10, eotaxin, IP-10, RANTES, MCP-1, MCP-3, and GRO-α were reduced, while IL-1β and MIP-2 were elevated at day 14. IL-13 and MIP-1β showed higher levels in the MI/R serum at day 14 than at day 7. mRNA levels of IL-4, IL-6, IL-13, and IL-27 were increased in the day 7 group compared to the sham, while MIP-1β, MCP-3, and GRO-α mRNA levels showed no significant difference between the MI/R and sham groups in blood mononuclear cells. Multiple CD4+ T-cell-associated cytokines/chemokines were upregulated in the MI/R hearts at the chronic stage. These results provided important evidence necessary for developing future immunomodulatory therapies after MI/R.